The Harmonization of Religion and The State: A Study of The Indonesia Context - Theguh Saumantri (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
Indonesian culture and civilization are supported by soft culture. Nature is so friendly to make the embodiment of Indonesia. The presence of religion and a harmonious state is proof that Indonesia is a peaceful country and free from regional conflicts. In a harmony of religion and state is always colored equal cooperation between the two. Religion has a broad role in realizing national development. Likewise with the State that always involves religious figures and organizations in controlling development. Religion must enlighten its people in order to accept and appreciate the basic values of statehood and the country must be able to protect all religious people. This research uses a library research method by making books and literature materials about religion and the state in Indonesia as references and primary sources in this study. From the results of the study it was concluded that in Indonesia religion and the country are not opposed even conflicted, but fill each other and strengthen, building cool relationships for the good of the people.